Arterial Supply to the Atrioventricular Node: Anatomical Variability and Clinical Implications - Tomokazu Kawashima (Arrhythmia & Electrophysiology Review, 2026)
Atrioventricular block (AVB) resulting from injury or ischaemia of the atrioventricular node (AVN) artery remains a key concern in inferior MI and procedures near the AVN. Given that ECG findings alone may be insufficient to reliably predict AVB occurrence or reversibility, anatomy-based risk assessment is essential. However, in vivo identification of the AVN artery is limited by its small size and marked anatomical variability and by the lack of specific markers for the AVN itself to confirm the artery’s terminal distribution. A main AVN artery typically arises near the cardiac crux and courses through the inferior pyramidal space, although its origin and trajectory vary. In addition, supplementary arterial supply may reach the node via anatomically distinct pathways, most commonly through the antero-inferior buttress of the atrial septum. These separate pathways variably contribute to nodal perfusion. Combined with positional variability of the AVN, this complexity limits precise anatomical risk stratification and may explain the heterogeneity of AVB occurrence and reversibility.